The Concept and Philosophy of Fiscal Policy in Modern and Islamic Historical Perspectives - Tamba, Dheddy Abdi; Janwari, Yadi; Hasanuddin, Muhammad; Ratnasari, Ai reni; Amany, Amany (Strata International Journal of Social Issues, 2025)
Fiscal policy is a fundamental tool for achieving macroeconomic goals such as economic stability, growth, and income equality. This study explores the concept and philosophy of fiscal policy, emphasizing its role in both modern and historical contexts, including its implementation during the Prophet Muhammad’s era. Employing a qualitative methodology with a literature review approach, the research analyzes fiscal policy instruments, including taxes, subsidies, debt, and state budget expenditures, particularly within the Indonesian context. Findings reveal that fiscal policy reflects Keynesian principles, emphasizing government intervention to address market inefficiencies, stabilize the economy, and promote equitable growth. Historical analysis highlights the philosophical alignment of fiscal policies during the Prophet Muhammad’s time with modern practices, focusing on justice, equality, and sustainability through instruments like zakat, kharaj, and wakaf. The study underscores the effectiveness of fiscal policy during crises, such as the COVID-19 pandemic, in mitigating severe economic impacts and fostering long-term development. To optimize fiscal policy, this research suggest that governments should enhance transparency, accountability, and technological integration to improve resource management and efficiency. Additionally, adopting principles of equity and sustainability from historical Islamic fiscal policies and fostering collaboration among stakeholders can address contemporary economic challenges while upholding philosophical foundations.